Preparation method of phase critical autocatalytic unsaturated polyester insulating resin

Preparing unsaturated polyester insulating resin through the phase critical autocatalytic method solves the problems in the existing technology that autocatalytic polyester is prone to electrical breakdown and catalyst corrosion, and achieves the preparation of resin with high insulation performance and temperature resistance.

CN119331229APending Publication Date: 2025-01-21GUANGZHOU XUHUA TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411312875.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-14
Filing Date
2024-09-20
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The autocatalytic polyester in existing volatile solvent-free insulating impregnated paints is prone to electrical breakdown, affecting the insulation performance, and small molecules of the catalyst may corrode electronic devices.

Method used

Use the critical self -catalytic legal preparation of unsaturated polyester insulating resin. By slowly heating to the critical temperature and gradually heating up to 240 ° C to avoid adding catalysts to form a high crystalline linear structure.

Benefits of technology

The preparation of insulating resin without catalyst addition is realized, which avoids the corrosion of electronic devices by the catalyst and improves the insulation performance and insulation temperature resistance level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331229A_ABST
    Figure CN119331229A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of phase critical autocatalytic unsaturated polyester insulating resin. The preparation method comprises the following steps: heating to a critical temperature of a first monomer dihydric alcohol and dihydric phenol or a second monomer dibasic acid and dibasic anhydride to initiate condensation polymerization activity so as to realize autocatalytic esterification reaction, and the whole reaction system does not contain small molecular catalysts such as organic acid or Lewis acid and the like. The epoxy resin does not contain a small molecule catalyst, avoids the potential risk that the small molecule catalyst corrodes an electronic device, does not contain amine structure polyhydric alcohol capable of enhancing hydroxyl nucleophilicity, and avoids the negative influence on the insulating property of the resin due to low bond energy and easy ionization of an amine structure. According to the invention, the phase critical autocatalysis system has esterification condensation polymerization activity, and the polyester resin has high insulation performance and does not have adverse effects on electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electric insulating resin preparation, and in particular relates to a method for preparing a phase-critical autocatalytic unsaturated ester insulating resin. Background Art

[0002] Insulating impregnating varnish is mainly used for insulating impregnation of electronic devices, including two categories: volatile solvent varnish and volatile solvent-free varnish. Volatile solvent varnish will emit a large amount of volatile organic compounds (VOCs) during use and curing process, which has an adverse impact on the environment and resources. Therefore, volatile solvent-free insulating impregnating varnish will gradually replace volatile solvent varnish and become the future development direction of insulating impregnating varnish.

[0003] Unsaturated polyester insulating varnish is a common main body in volatile solvent-free varnish due to its good bonding performance. It is the main component that affects the insulating performance of insulating varnish. The insulating varnish is generally composed of unsaturated polyester resin, diluent (containing unsaturated bonds) and initiator (photoinitiator or thermal initiator). Patent application with publication number CN111440518A provides a preparation method of unsaturated insulating impregnated polyester, using p-toluenesulfonic acid as a catalyst. In the application of insulating impregnated varnish, small molecule catalysts such as organic acids or Lewis acids commonly used in the preparation of polyester cause corrosion to electronic devices; in order to avoid the influence of catalysts, polyester can be synthesized by autocatalysis. Patent applications with publication numbers CN115785418A and CN107980047A both provide a preparation method of autocatalytic polyester polyols. The common feature of their autocatalysis is the use of diols or polyols containing amine structures, wherein the strong electron-donating ability of the amine structure greatly enhances the nucleophilicity of the alcohol hydroxyl group, thereby autocatalyzing the condensation of polyester. However, the amine structure contained in the above-mentioned self-catalytic polyester polyol has low bond energy and is easily ionized, which makes the polyester susceptible to electrical breakdown and seriously affects the insulation performance. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a phase-critical autocatalytic unsaturated polyester insulating resin, which does not use a catalyst and does not contain a structure with low bond energy and easy ionization, and has good insulating properties. The unsaturated polyester insulating resin is prepared by phase-critical autocatalysis, which has good insulating properties and does not corrode electronic devices in practical applications.

[0005] Technical solution: In order to achieve the above object, the present invention adopts the following technical solution: a method for preparing a phase-critical autocatalytic unsaturated ester insulating resin, comprising the following steps:

[0006] Step (1): adding a first monomer, a second monomer, a polymerization inhibitor and an antioxidant into a reaction kettle, and slowly heating the reaction kettle to a phase critical temperature;

[0007] Step (2): gradually raise the temperature of the system to 240°C and react for 4-30 hours;

[0008] Step (3): remove moisture and small molecular weight esters by vacuuming at 240° C. to obtain unsaturated polyester insulating resin.

[0009] Preferably, the first monomer in step (1) is a diol or diphenol with good electrical properties, specifically one or more of neopentyl glycol, bisphenol A, and hydrogenated bisphenol A;

[0010] Preferably, the second monomer in step (1) is one or more of isophthalic acid, phthalic acid, terephthalic acid, phthalic anhydride, maleic anhydride and maleic acid;

[0011] Preferably, in step (1), the molar ratio of the first monomer to the second monomer is (1-2):1, more preferably (1-1.2):1;

[0012] Preferably, the polymerization inhibitor in step (1) is one or more of p-hydroxyanisole, tert-butylhydroquinone, and p-tert-butylcatechol; the added amount is 0.1% to 0.5% of the total mass of the system, and more preferably 0.2%;

[0013] Preferably, the antioxidant in step (1) is 2,6-di-tert-butyl-4-methylphenol; the added amount is 1% to 5% of the total mass of the system, and more preferably 3%;

[0014] Preferably, the feeding in step (1) is one or more times;

[0015] Preferably, the phase critical temperature in step (1) is the phase critical temperature of the first monomer or the second monomer in the reaction substrate;

[0016] Preferably, the gradual temperature increase in step (2) is 10° C. every 1 to 3 hours, and more preferably 10° C. every 1.5 to 2 hours;

[0017] Preferably, the vacuuming in step (3) is to use a water circulating vacuum pump to gradually increase the vacuum degree until it is completely vacuumed;

[0018] Preferably, the vacuuming time in step (3) is 1 to 2 hours of complete vacuum;

[0019] Preferably, the discharge temperature in step (3) is 120-130°C.

[0020] The second object of the present invention is to provide an unsaturated ester insulating resin obtained by the above preparation method.

[0021] Beneficial effects: (1) The unsaturated polyester insulating resin prepared by self-catalysis of the present invention does not require the addition of a catalyst, thereby avoiding the corrosion of electronic devices by small catalyst molecules;

[0022] (2) The unsaturated polyester insulating resin prepared by autocatalysis of the present invention does not contain structures with low bond energy and easy ionization, thus ensuring excellent insulating properties;

[0023] (3) The unsaturated polyester insulating resin prepared by self-catalysis of the present invention has a highly crystalline linear structure, which improves its insulation temperature resistance level. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the infrared spectrum of the raw materials used in the preparation process described in Example 1 and the product unsaturated polyester resin. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Unless otherwise specified, the added materials in the examples and comparative examples of the present invention are calculated by weight.

[0027] Embodiment 1:

[0028] 150 parts of neopentyl glycol, 80 parts of isophthalic acid, 80 parts of maleic anhydride, 1.55 parts of p-hydroxyanisole, and 9.3 parts of 2,6-di-tert-butyl-4-methylphenol were added to the reactor at once, and the temperature was slowly raised to 150°C, the critical temperature of the neopentyl glycol phase. After reacting at this temperature for 2 hours, the temperature was raised by 10°C every 1.5 hours under the condition of 160-240°C, and the total reaction time was 15.5 hours. At 240°C, a vacuum pump was used to evacuate the water and small molecular esters, and the vacuum degree was gradually increased until it was completely vacuumed and maintained for 2 hours. The vacuum was removed and the temperature was cooled to 120°C with stirring to obtain the unsaturated polyester insulating resin. Figure 1 As shown in the figure, it is the infrared spectrum of the raw materials used in the preparation process described in this embodiment and the unsaturated polyester resin as the product. Specifically, neopentyl glycol has an infrared spectrum of 3326 cm -1 and unsaturated polyester resin at 3539cm -1 There are characteristic peaks of hydroxyl groups on the -1There are characteristic peaks of methyl and methylene on the unsaturated polyester, which proves that the unsaturated polyester contains neopentyl glycol structural segments. The unsaturated bonds of the unsaturated polyester resin are provided by maleic anhydride. The peaks of maleic anhydride and unsaturated polyester resin are at 1586-1640cm -1 There are characteristic peaks of carbon-carbon double bonds on both surfaces, and the unsaturated polyester resin has a peak at 729 cm -1 The peaks of benzene rings are similar to those of isophthalic acid. The peaks of isophthalic acid and maleic anhydride are at 1550-1650cm -1 There is a characteristic peak of carbonyl, while the carbonyl peak of unsaturated polyester is at 1725cm -1 , confirming that the unsaturated polyester resin contains structural segments of isophthalic acid and maleic anhydride. In summary, the unsaturated polyester covers the functional group characteristic peaks of all raw materials, and the unsaturated polyester resin is successfully prepared.

[0029] Embodiment 2:

[0030] This embodiment is substantially the same as embodiment 1, except that the feed materials are 138 parts of neopentyl glycol, 80 parts of isophthalic acid, 80 parts of maleic anhydride, 1.49 parts of p-hydroxyanisole, and 8.94 parts of 2,6-di-tert-butyl-4-methylphenol.

[0031] Example 3

[0032] This embodiment is substantially the same as embodiment 1, except that the feed materials are 150 parts of neopentyl glycol, 125 parts of isophthalic acid, 53 parts of maleic anhydride, 1.65 parts of p-hydroxyanisole, and 9.87 parts of 2,6-di-tert-butyl-4-methylphenol.

[0033] Example 4

[0034] This embodiment is basically the same as embodiment 1, except that the feeding is a secondary feeding, the first feeding is 80 parts of neopentyl glycol, 80 parts of isophthalic acid, 1.55 parts of p-hydroxyanisole, and 9.3 parts of 2,6-di-tert-butyl-4-methylphenol, which are put into the reactor, and the temperature is slowly raised to 150°C, the critical temperature of the neopentyl glycol phase, and the temperature is raised after reacting for 2 hours at this temperature. The temperature is raised by 10°C every 1.5 hours under the condition of 160-200°C, and the reaction is carried out for a total of 9.5 hours, and then the temperature is lowered to 130°C before secondary feeding, the second feeding is 70 parts of neopentyl glycol and 80 parts of maleic anhydride, and the temperature is raised after reacting for 2 hours at this temperature. The temperature is raised by 10°C every 1.5 hours under the condition of 160-240°C, and the reaction is carried out for a total of 15.5 hours.

[0035] Example 5

[0036] This embodiment is basically the same as Embodiment 4, except that the first feed is 125 parts of neopentyl glycol, 125 parts of isophthalic acid, 1.65 parts of p-hydroxyanisole, and 9.87 parts of 2,6-di-tert-butyl-4-methylphenol, and the second feed is 25 parts of neopentyl glycol and 53 parts of maleic anhydride.

[0037] Example 6

[0038] This embodiment is basically the same as Embodiment 1, except that the first feed is 80 parts of neopentyl glycol, 80 parts of isophthalic acid, 1.97 parts of p-hydroxyanisole, and 11.82 parts of 2,6-di-tert-butyl-4-methylphenol, and the second feed is 154 parts of hydrogenated bisphenol A and 80 parts of maleic anhydride.

[0039] Example 7

[0040] This embodiment is substantially the same as the embodiment 1, except that the feed materials are 150 parts of neopentyl glycol, 80 parts of isophthalic acid, 94.5 parts of maleic acid, 1.62 parts of p-hydroxyanisole, and 9.74 parts of 2,6-di-tert-butyl-4-methylphenol.

[0041] Comparative Example 1

[0042] This embodiment is substantially the same as embodiment 1, except that the feed materials are 150 parts of neopentyl glycol, 150 parts of isophthalic acid, 80 parts of maleic anhydride, 1.9 parts of p-hydroxyanisole, and 11.4 parts of 2,6-di-tert-butyl-4-methylphenol.

[0043] Comparative Example 2

[0044] This embodiment is substantially the same as the embodiment 1, except that the feed materials are 200 parts of neopentyl glycol, 80 parts of isophthalic acid, 80 parts of maleic anhydride, 1.8 parts of p-hydroxyanisole, and 10.8 parts of 2,6-di-tert-butyl-4-methylphenol.

[0045] Comparative Example 3

[0046] This embodiment is substantially the same as the embodiment 1, except that the feed materials are 153 parts of diethylene glycol, 80 parts of isophthalic acid, 80 parts of maleic acid, 1.57 parts of p-hydroxyanisole, and 9.39 parts of 2,6-di-tert-butyl-4-methylphenol.

[0047] In order to verify the autocatalytic polycondensation activity and performance of the phase critical autocatalytic unsaturated polyester insulating resin of the present invention, the products of Examples 1-7 and Comparative Examples 1-3 were subjected to reaction end point acid value, electrical breakdown voltage and corrosion tests, and the test methods are as follows:

[0048] Acid value test:

[0049] According to the standard GB / T 6743-1986;

[0050] Paint film breakdown strength test:

[0051] Implemented in accordance with standard HGT3330-1980 (1985);

[0052] Corrosion testing:

[0053] The products of Examples 1-7 of the present invention and Comparative Examples 1-3 were mixed evenly with the thermal initiator DCP (the amount of DCP added was 0.2% of the resin mass), laid on a test substrate PCB board with a thickness of 0.3 mm, baked in an oven at 150° C. for 2 hours, and then subjected to a 180-day storage test to observe the corrosion of the PCB board.

[0054] Table 1 Product performance test results of Examples 1-7 and Comparative Examples 1-3

[0055]

[0056] As can be seen from the results in Table 1, none of the embodiments 1-7 and comparative examples 1-3 of the present invention used a catalyst, and no abnormality occurred in the corrosion test; the molar ratio of the feed materials of embodiments 1-7 was within the range of 1: (1 to 1.2), and the acid values ​​of embodiments 1-7 were finally measured to be less than 3 mgKOH / g, indicating that the basic reaction was complete, and the breakdown voltage strength of embodiments 1-7 was greater than 6 kv / mm, and had relatively good insulation performance; the carboxyl ratio in the molar ratio of the feed materials of comparative example 1 was higher than the range described in the present invention, and the acid value was finally measured to be Greater than 35 mgKOH / g (theoretical 41.11 mgKOH / g); The proportion of hydroxyl groups in the molar ratio of the feed in comparative example 2 is higher than the range described in the present invention, and the final measured acid value is less than 3 mgKOH / g, but its hydroxyl value is much greater than that of Example 1, which is caused by a large amount of unreacted neopentyl glycol in the system; Comparative example 3 replaced diethylene glycol, although the reaction was basically complete and the final measured acid value was less than 3 mgKOH / g, because the central carbon atom of diethylene glycol was not electrically neutral, its electrical insulation performance was significantly deteriorated. In summary, the product obtained by the scheme of the present invention has good insulation performance after reacting with the thermal initiator DCP, and no catalyst is added, which avoids the corrosion of small catalyst molecules to electronic devices. It does not contain structures with low bond energy and easy ionization, ensuring excellent insulation performance. It is a highly crystalline linear structure, which improves its insulation temperature resistance level.

[0057] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention as defined in the appended claims.

Claims

1. A method for preparing a phase-critical autocatalytic unsaturated ester insulating resin, characterized in that The steps include: (1) adding a first monomer, a second monomer, a polymerization inhibitor, and an antioxidant into a reaction kettle, and slowly heating the kettle to a phase critical temperature; (2) gradually raising the temperature of the system to 240°C and reacting for 4-30 hours; (3) removing moisture and small molecular weight esters by vacuuming at 240° C. to obtain unsaturated polyester insulating resin; Wherein: the first monomer is a dihydric alcohol or a dihydric phenol; The second monomer is a dibasic acid or a dibasic acid anhydride or a mixture of the two.

2. The method for preparing the phase critical autocatalytic unsaturated ester insulating resin according to claim 1, characterized in that: The first monomer is one or more of neopentyl glycol, bisphenol A, and hydrogenated bisphenol A.

3. The method for preparing the phase critical autocatalytic unsaturated ester insulating resin according to claim 1, characterized in that: The second monomer is one or more of isophthalic acid, phthalic acid, terephthalic acid, phthalic anhydride, maleic anhydride and maleic acid.

4. The method for preparing the phase critical autocatalytic unsaturated ester insulating resin according to claim 1, characterized in that: In step (1), the molar ratio of the first monomer to the second monomer is (1-2):

1.

5. The method for preparing the phase critical autocatalytic unsaturated ester insulating resin according to claim 1, characterized in that: The feeding process of step (1) is one-time feeding or multiple feedings.

6. The method for preparing the phase critical autocatalytic unsaturated ester insulating resin according to claim 1, characterized in that: The phase critical temperature in step (1) is the phase critical temperature of the first monomer or the second monomer in the reaction substrate.

7. The method for preparing the phase critical autocatalytic unsaturated ester insulating resin according to claim 1, characterized in that: The inhibitor in step (1) is one or more of p-hydroxyanisole, tert-butylhydroquinone, and p-tert-butylcatechol.

8. The method for preparing the phase critical autocatalytic unsaturated ester insulating resin according to claim 1, characterized in that: The antioxidant in step (1) is 2,6-di-tert-butyl-4-methylphenol.

9. An unsaturated ester insulating resin obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Flame retardant and auto-catalytic polyesters for polyurethanes

    CN107980047A

  • High-heat-resistance environment-friendly refrigerant-resistant insulating impregnating resin and preparation method thereof

    CN111440518A

  • Polyester polyol and preparation method thereof, and soft polyurethane foam

    CN115785418A